2011
DOI: 10.6004/jnccn.2011.0088
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Radiation Therapy Within the German Hodgkin Study Group Trials

Abstract: Since its beginning, more than 16,000 patients have been enrolled in the multicentric randomized trials of the German Hodgkin Study Group (GHSG) for adult patients. Within 6 study generations, the treatment of Hodgkin lymphoma has been developed stepwise by using the results of the completed protocols. Now the sixth generation is active. According to the role of radiotherapy, the study group successfully evaluated different dose-effect relationships and could also prove the efficacy of involved-field radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Based on these findings, radiation therapy is no longer considered a component of the standard of care for initial treatment of adult limited-stage HL. 3 Consistent with our findings, clinical studies suggest that, because effective salvage therapy is available, pediatric HL outcomes may be improved by considering overall, not just primary treatment, 22 and long-term outcomes may be more important than low early relapse rate. 23 Indeed, consideration of late effects may be even more important for pediatric patients given the probable higher risk of late effects from exposure during adolescent years, although more complicated because of the long periods of follow-up needed to adequately capture late mortality risks.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Based on these findings, radiation therapy is no longer considered a component of the standard of care for initial treatment of adult limited-stage HL. 3 Consistent with our findings, clinical studies suggest that, because effective salvage therapy is available, pediatric HL outcomes may be improved by considering overall, not just primary treatment, 22 and long-term outcomes may be more important than low early relapse rate. 23 Indeed, consideration of late effects may be even more important for pediatric patients given the probable higher risk of late effects from exposure during adolescent years, although more complicated because of the long periods of follow-up needed to adequately capture late mortality risks.…”
supporting
confidence: 89%
“…Although radiation is no longer standard of care for all low-and intermediate-risk adult patients, it continues to be used for pediatric patients. 3 Clinical studies suggest that chemotherapy alone (CT) can achieve disease control in a large proportion of patients, with radiation therapy used only for the subset who fail initial treatment or require salvage therapy after relapse. Because therapy for refractory or relapsed lymphoma involves higher doses of radiation and chemotherapy, patients who relapse face elevated risks for both second cancer and cardiac late-effects mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Given the low overall relapse rate (5·1%) and the excellent outcome of cases with mediastinal bulk (CR: 94%, 5‐year EFS: 89·7%), ABVD DD‐DI corresponds with the HD15 trial in supporting the redundancy of consolidation radiotherapy in patients who are PET‐negative following upfront intensified regimens (Eich et al , ; Engert et al , ). Indeed, while the proportion of patients receiving radiotherapy progressively reduced through the GHSG studies, from 71% (HD9) to 38% (HD12) down to 11% (HD15) (Engert et al , , ; Eich et al , ), at least one half (46–67%) of patients accrued in most recent trials of standard ABVD was still irradiated (Gobbi et al , ; Federico et al , ; Viviani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…27 In general, a multimodality approach of TTE with complementary CT or MRI can facilitate diagnosis of post-radiation constrictive pericarditis (Table 2). 13 -ammonia PET perfusion in a 58-year-old female 8 years post-mediastinal radiation, demonstrating a medium-sized perfusion defect of moderate intensity in the mid-anteroseptal, mid-inferoseptal walls, the apical septum, apical inferior wall and apex that was partly reversible, consistent with ischaemia in the distribution of the mid-left anterior descending artery. In addition, there was a medium-sized defect of moderate intensity in the entire inferolateral wall that was reversible, consistent with ischaemia in the distribution of an obtuse marginal artery.…”
Section: Post-radiation Pericardial Diseasementioning
confidence: 88%
“…11 Contemporary IFRT regimens for Hodgkin's lymphoma involve total doses of approximately 35 Gy delivered in 20 daily fractions to the supra-diaphragmatic lymph node areas 12 ; whereas a lower total dose of 20 Gy for earlier stages has been advocated. 13 For any cancer type, it has long been known that radiation doses above 30 Gy are associated with cardiac damage. A recent, large population-based case -control study of 2168 women treated with radiation therapy for breast cancer over 5 decades reported an increase in rate of major coronary events of 7.4% per Gy [95% confidence interval (CI) 2.9 -14.5; P , 0.001], with no apparent threshold below which there was no increased risk.…”
Section: Basics Of Radiotherapymentioning
confidence: 99%